MEMPERKUAT KARAKTER MELALUI LANDASAN FILOSOFI MENGGALI POTENSI PESERTA DIDIK DI SEKOLAH DASAR - Ade Islamiati; Neviyarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to discuss the importance of strengthening children's character through a philosophical approach in the elementary school environment. This article underlines that character education does not only involve cognitive, but also emotional, social, and moral aspects. The author explains that a philosophical foundation can be a strong basis for building good character in students. Philosophy provides a deep understanding of the principles and values that underlie human life. In an educational context, philosophy can help shape children's attitudes, personality and morals. This study also discusses several practical approaches that can be used by educators in elementary schools to explore the potential of students through a philosophical foundation. One approach highlighted is the Socratic approach, in which teachers encourage students to think critically, ask questions, and actively participate in discussions. This approach helps to develop higher thinking skills, broaden horizons, and deepen understanding of philosophical values. Through this approach, students are expected to develop strong characters, such as honesty, discipline, responsibility, and empathy. They will also be able to handle conflict wisely, make good decisions, and have a deeper understanding of their purpose in life. And also the need to strengthen the character of students through a philosophical foundation in elementary schools. This approach can help build a generation that has moral integrity, critical thinking, and the ability to forge healthy relationships with others.